Practical Povidone Iodine Catalyzed Synthesis of 2,5-Disubstituted Oxazoles from Acetophenones and α-Amino Acids - Wang, Jian; Sun, Xue-Qin; Li, Meng-Fei; Wang, Shao-Dong; Ren, Jiangmeng; Zeng, Bu-Bing (Synlett, 2025)
Nonharmful povidone iodine (PVP-I) was applied in the cyclization of acetophenones and α-amino acids to give 2,5-disubstituted oxazoles. Acetophenones with different substituents and natural α-amino acids were applied to our developed method, and more than 38 2,5-disubstituted oxazole compounds were obtained in moderate to good yields. Several naturally active 5-(3-indolyl)oxazole alkaloids such as pimprinine, labradorin, and pimprinol were successfully acquired in moderate yields using this strategy.
Keywords: povidone iodine; acetophenones; α-amino acids; oxazoles; 5-(3-indolyl)oxazole alkaloids